Understanding psychoanalytic work online and back to the couch in the wake of the COVID-19 pandemic: an investigation among Italian psychoanalysts - Reatto, Licia Lea; Werbart, Andrzej; Oasi, Osmano; De Salve, Francesca; Ierardi, Elena; Giordano, Mattia; Riva Crugnola, Cristina (Frontiers in Psychology, 2023)
Background Worldwide, psychotherapists’ clinical experience went through rapid developments with transition to teletherapy during the COVID-19 pandemic. Literature on the use of remote psychoanalysis was not conclusive, leaving the issue of the consequences of the necessary setting alternation open. This study aimed to investigate the psychoanalysts’ experiences of shifting to remote work and then returning to in-person setting, considering the effect of the patients’ attachment styles and personality configurations. Method Seventy-one analysts of the Italian Psychoanalytic Society were asked to fill out an online survey about patients who found the transition easier and patients who found it more difficult. General questions on therapeutic work, ISTS (Interpretive and Supportive Technique Scale) for interpretive and supportive aspects of technique, WAI-S-TR (Working Alliance Inventory-Short Revised-Therapist) for therapeutic alliance, RQ (Relationship Questionnaire) for attachment style, and PMAI (Prototype Matching of Anaclitic-Introjective Personality Configuration) for personality configurations were administered. Results All of the analysts chose to continue the treatment using audio-visual tools. Patients with difficult transitions had a significantly higher frequency of insecure attachment and a higher score on RQ Dismissing scale than patients with easy transitions. No significant differences were found between the two groups in personality configurations, psychotherapeutic alliance, and psychotherapeutic technique. Moreover, a higher level of therapeutic alliance was positively correlated to RQ Secure scale and was negatively correlated to RQ Dismissing scale. Patients with easy transition both to remote work and back to in-person setting had higher scores of therapeutic alliances than those with difficult transition both to remote work and back to in-person setting. Conclusion Online psychoanalytic therapy was widely used during the COVID-19 pandemic. Patients with insecure attachment styles had greater difficulties in adapting to setting alternations, thus confirming that insecure attachment is a vulnerability factor not only for psychopathological problems but also for a well-functioning therapeutic collaboration. Patient’s personality configuration did not influence their adaptation to the setting alternation. The supportive and interpretive styles did not undergo significant changes in the transition from in-person setting to remote setting and vice versa, thus suggesting a continuity in the analysts’ “internal setting.”